2010
DOI: 10.1158/1078-0432.ccr-09-2697
|View full text |Cite
|
Sign up to set email alerts
|

Defucosylated Humanized Anti-CCR4 Monoclonal Antibody KW-0761 as a Novel Immunotherapeutic Agent for Adult T-cell Leukemia/Lymphoma

Abstract: Purpose: Adult T-cell leukemia/lymphoma (ATLL) has a very poor prognosis. We have developed the humanized defucosylated anti-CC chemokine receptor 4 (CCR4) monoclonal antibody KW-0761 as a next generation immunotherapeutic agent. The first aim of the present study was to evaluate whether the antitumor activity of KW-0761 would likely be sufficient for therapeutic clinical application against ATLL. The second aim was to fully elucidate the mechanism of antibody-dependent cellular cytotoxicity (ADCC) mediated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
174
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 221 publications
(183 citation statements)
references
References 47 publications
4
174
0
1
Order By: Relevance
“…We have shown that a therapeutic anti-CCR4 mAb does deplete Treg cells in vitro (39,40) and in vivo in humanized mice (27). Furthermore, we confirmed the CD25 + CD4 + FOXP3 + Treg depletion activity mediated by the humanized anti-CCR4 mAb mogamulizumab (KW-0761) in humans (41)(42)(43)(44). Therefore, a combination of Tax-CTL adoptive immunotherapy with mogamulizumab to act not only as an anti-ATL agent but also to deplete Treg cells would be promising.…”
Section: Discussionsupporting
confidence: 60%
“…We have shown that a therapeutic anti-CCR4 mAb does deplete Treg cells in vitro (39,40) and in vivo in humanized mice (27). Furthermore, we confirmed the CD25 + CD4 + FOXP3 + Treg depletion activity mediated by the humanized anti-CCR4 mAb mogamulizumab (KW-0761) in humans (41)(42)(43)(44). Therefore, a combination of Tax-CTL adoptive immunotherapy with mogamulizumab to act not only as an anti-ATL agent but also to deplete Treg cells would be promising.…”
Section: Discussionsupporting
confidence: 60%
“… 136     Potent anti-tumor effect of KM2760 in NOG mice bearing adult T cell leukemia/lymphoma (ATLL) cellsIto et al 137 Mogamulizumab/ POTELIGEO/ KM0761CC chemokine receptor 4 (CCR4)afucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Induced potent tumor growth inhibition and enhanced survival in ATLL tumor-bearing mice over vehicle controlIshii et al. 138 Humanized IgG1     Benralizumab /MEDI-563Humanized IgG1IL-5RαafucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Efficient eosinophils depletion in non-human primatesKolbeck et al. 123 KHK2823     Humanized IgG1IL-3Rα (CD123)afucosylatedFUT8 −/− CHO cells (Potelligent® Technology)Tumor growth inhibition of human AML cell line MOLM-13 grafted into nude rats compared to vehicle control(e)    Significant depletion of IL-3Rα-positive cells in the peripheral blood of cynomolgus monkeys Low fucose Elotuzumab/ HuLuc63-LFSignaling Lymphocyte Activation Molecule (SLAMF7, also called CS1)ReducedYB2/0 cellsEnhanced anti-tumor activity in OPM2 xenograft SCID mice modelHsi et al.…”
Section: Enhanced Adcc Activities By Afucosylated Antibodies In In VImentioning
confidence: 99%
“…GA101 (obinutuzumab) is a GE, type II anti-CD20 mAb that has recently been approved by the U.S. Food and Drug Administration for the first line treatment of patients with chronic lymphocytic leukemia (CLL) in combination with chlorambucil (18)(19)(20). In Japan, the GE CCR4 Ab mogamulizumab has been approved for treatment of patients with relapsed or refractory CCR4 + T cell leukemia-lymphoma (21).…”
mentioning
confidence: 99%